2022
DOI: 10.1108/jcefts-03-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic and institutional conditions: the drivers behind divestment of FDI in Sub-Saharan Africa

Abstract: Purpose The purpose of this paper is to determine how macroeconomic performance work with institutional quality influences divestment of foreign direct investment (FDI) in Sub-Saharan Africa, in the short and long run. Design/methodology/approach This paper investigates divestment of FDI in Sub-Saharan Africa, within the period 1980–2020. The investigation is undertaken by first comparing the trend with what is obtained in other economic regions of the world. The factors behind the divestment are subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…AGFD is measured as the negative of the agricultural net inward FDI. The recognition of AGFD as the negative of the net AGFDI inflow has been acknowledged by the United Nations [50][51][52] and others [24,53,54]. FD is measured by the balance of payments (BOP) and the directional (DA) approaches [55].…”
Section: Model and Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…AGFD is measured as the negative of the agricultural net inward FDI. The recognition of AGFD as the negative of the net AGFDI inflow has been acknowledged by the United Nations [50][51][52] and others [24,53,54]. FD is measured by the balance of payments (BOP) and the directional (DA) approaches [55].…”
Section: Model and Modellingmentioning
confidence: 99%
“…Existing literature has shown that the drivers of IFDI are the macroeconomic factors such as inflation, exchange rate, trade, and savings rate among others [66][67][68][69]. Also, these factors drive the divestment of IFDI [53,70]. Economic managers in developing countries must, therefore, keep their fingers on these indicators.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Various foreign divestment theories such as the eclectic paradigm, divestiture, institutional-based view, real options and neoclassical, have been employed by scholars to better understand foreign divestment (see Matekenya & Moyo, 2023;Konara & Ganotakis, 2020;Arte & Larimo, 2019;Musshoff, Odening, Schade, Maart-Noelck & Sandri, 2013;Edo & Nnadozie, 2023). The theoretical foundation of this paper is derived from the existing literature on foreign divestment.…”
Section: Conceptual and Theoretical Reviewmentioning
confidence: 99%
“…The real options theory suggests that subsidiaries can add value in uncertain international markets and host country conditions (Belderbos & Zou, 2009). Finally, neoclassical theory suggests that return on investment significantly influences capital flows across countries, with high returns in low-capital countries attracting investment towards poorer nations (Edo & Nnadozie, 2023).…”
Section: Conceptual and Theoretical Reviewmentioning
confidence: 99%
“…Sartor and Beamish (2020) stated that multinational corporations find it more difficult to manage and control the behaviour of their subsidiaries when dealing with increased levels of political corruption, which increases the likelihood that they will divest. Edo and Nnadozie (2022), on the other hand, examined the institutional conditions for FDI divestment in Sub-Saharan Africa, suggesting the opposite impact. The empirical findings show that in Sub-Saharan Africa, poor institutional quality accelerates outflows and drives divestment.…”
Section: Literature Reviewmentioning
confidence: 99%